The Impact of The Implementation of Goal Setting Theory and Agency Theory on Performance: Evidence from Indonesian Public Sector Organizations - ANITA PRIMASTIWI; HARDO BASUKI (The Indonesian Journal of Accounting Research, 2013)
The aim of this study is to give empirical evidence about theimpact of the implementation of goal setting theory andagency theoryon the performance of local governmental units in the Special Regionof Yogyakarta Province. The samples were the SKPD’s chairmen or chairwomenwho lead the governmental services atthe province level (D IYogyakarta) and the regency level (Kota Yogyakarta, KabupatenSleman,Kabupaten Gunung Kidul, Kabupaten Bantul, and KabupatenKulon Progo), and they must be in their term of office for at least oneyear. This study analyzed their perceptions about the statements in thequestionaire. The data were analized by partial least square (PLS) withSmart PLS Version 2.0. The findings showed empirical evidence of theimpact of clear and measurable goals on qualitative and quantitativeperformance, and the impact of performance measurement indicatorson quantitative and qualitative performance are consistent withgoalsetting theory, but the impact of decentralization on the quantitativeand qualitative performance is inconsistent with goal setting theory.The results show that the impact of incentives on the quantitative andqualitative performance isinconsistent with agency theory.